Indonesia’s young consumers’ green purchase intention: understanding the effect of price sensitivity & knowledge - Saragi, Edwardo Yeremia (Universitas Negeri Surabaya, Indonesia, 2025)
The global plastic waste crisis is escalating, with Indonesia as a major contributor due to high consumption and weak waste management. Eco-friendly bottled mineral water made from recycled materials offers a sustainable option targeting Millennials and Gen Z, who show strong potential for adopting green products. However, gaps between attitudes and purchase intentions remain, requiring investigation into the roles of perceived value, knowledge, and price sensitivity. This study examines the effects of green perceived value (five dimensions), perceived knowledge, attitude, subjective norm, trust, and price sensitivity on green purchase intention, with price sensitivity as a moderator. Based on 504 respondents analysed using PLS-SEM, perceived knowledge significantly influences green perceived value, attitude, and trust. All green perceived value dimensions contribute strongly to the construct. Attitude, subjective norm, and trust positively affect green purchase intention, with attitude and trust as dominant factors. Price sensitivity reduces purchase intention, weakens the effect of subjective norm, but does not alter the attitude–purchase intention link. These findings suggest that personal evaluations and trust remain stable drivers, while social norms are more vulnerable to price pressures.